Developing English Learning Materials for Food and Beverage Service in Singaraja Hotel School - Praptono, Gede Sudana; Artini, Putu; Suarnajaya, I Wayan (Journal of Education Technology, 2020)
This research aimed at developing English learning material for food and beverage service in Singaraja Hotel School for D1 program. The research design followed 4D model. The steps of this study were: (1) Define,(2) Design, (3)Develop, and (3)Disseminate. There were two questionnaires employed in the research: (1) Needs analysis questionnaire (2) Expert judgment questionnaire. The materials needed are the English learning materials consisted of various activities and example for food and beverage service course. The activities of the materials were in the form of dialogues, detail explanation, illustration, and additional information related to food and beverage service course. Based on the data process, it was found that the score of the product quality was 256. Based on the criteria made, it can be concluded that the quality of the product was categorized as good material. It means that the materials can be used in learning process.